Toll‐like receptor‐4 299Gly allele is associated with Guillain‐Barré syndrome in Bangladesh - Jahan, Israt (Ann Clin Transl Neurol, 2019)
OBJECTIVE: TLR4 plays an important role in the pathogenesis of Guillain‐Barré syndrome (GBS). The relationships between TLR4 polymorphisms and susceptibility to GBS are poorly understood. We investigated the frequency and assessed the association of two single nucleotide polymorphisms (SNPs) in the extracellular domain of TLR4 (Asp299Gly and Thr399Ile) with disease susceptibility and the clinical features of GBS in a Bangladeshi cohort. METHODS: A total of 290 subjects were included in this study: 141 patients with GBS and 149 unrelated healthy controls. The TLR4 polymorphisms Asp299Gly and Thr399Ile were genotyped using polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) assay. RESULTS: The minor 299Gly allele was significantly associated with GBS susceptibility (P = 0.0137, OR = 1.97, 95% CI = 1.17–3.31), and was present at a significantly higher frequency in patients with the acute motor axonal neuropathy (AMAN) subtype of GBS (P = 0.0120, OR = 2.37, 95% CI = 1.26–4.47) than acute inflammatory demyelinating polyneuropathy (AIDP) subtype (P = 0.961, OR = 1.15, 95% CI = 0.38–3.48); when compared to healthy controls. The genotype frequency of the Asp299Gly polymorphism was not significantly different between patients with GBS and healthy controls. The Asp299‐Thr399 haplotype was associated with a significantly lower risk of developing GBS (P = 0.0451, OR = 0.63, 95% CI = 0.40–0.99). No association was observed between the Thr399Ile polymorphism and GBS disease susceptibility. INTERPRETATION: The TLR4 minor 299Gly allele was associated with increased susceptibility to GBS and the axonal GBS subtype in the Bangladeshi population. However, no associations were observed between the genotypes of the Asp299Gly and Thr399Ile SNPs and antecedent C. jejuni infection or disease severity in Bangladeshi patients with GBS.